The relationship between visceral adiposity and cardiometabolic risk in Chinese women with polycystic ovary syndrome. Issue 6 (November 2021) - Ng, N.Y.H.; Liu, K.H.; Tam, C.H.T.; Jiang, G.; Cheng, F.; Hou, Y.; Yau, T.T.; Ozaki, R.; Chan, M.H.; Lim, C.K.; Sahota, D.S.; Li, T.C.; et al.
Abstract: Objective: To compare the extent to which visceral adiposity, as measured by mesenteric fat thickness, contribute to cardiometabolic risk, especially insulin resistance, in women with PCOS and healthy control. Methods: This is a cross-sectional study with a total of 190 women with PCOS fulfilling the Rotterdam diagnostic criteria. Women without PCOS were recruited from a previous study, which comprised 416 healthy women controls with normal glucose tolerance. All subjects underwent OGTT, biochemical assessment, and sonographic assessment with measurements of mesenteric, preperitoneal and subcutaneous fat thickness. Results: Mesenteric fat thickness was strongly correlated to cardiometabolic traits including blood pressure, fasting and 2-h glucose, triglycerides, HOMA-IR; and was negatively correlated to HDL-C in both cohorts (all p < 0.01). In PCOS, positive correlation was observed between mesenteric fat thickness and free androgen index ( p < 0.01). Compared with controls, the regression line between mesenteric fat and HOMA-IR is much steeper in PCOS ( p < 0.01). Conclusion: Women with PCOS remain more insulin resistant compared to controls at any given degree of visceral adiposity.